THE LEGAL CHALLENGES OF LAWS AND DRONES - Andrei-Alexandru STOICA (Challenges of the Knowledge Society)
The rapid development and deployment of Lethal Autonomous Weapons Systems (LAWS) and drones have raised significant legal, ethical, and operational challenges for the entire international community. This paper examines the implications of these technologies within the context of international law, focusing on the principles of sovereignty, accountability, and compliance with humanitarian law. It discusses the potential risks posed by autonomous decision-making in warfare, including the lack of human oversight and the challenges in assigning responsibility for unlawful actions. Furthermore, the paper explores existing frameworks, such as the Geneva Conventions and the Convention on Certain Conventional Weapons, in addressing the use of LAWS and drones, while considering the limitations of these treaties in regulating emerging technologies. Finally, the research proposes recommendations for the development of new legal norms that balance technological advancements with human rights and international security concerns.